Representasi Post Traumatic Stress Disorder dalam Film Berbalas Kejam (Analisis Semiotika John Fiske) - Ariyanti, Sheilla Putri; Rahmawati, Aulia (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Films are not only a medium of entertainment, but also reflect social and psychological issues in society. Film Berbalas Kejam (2023) raises the issue of Post-Traumatic Stress Disorder (PTSD) through the main character named Adam, a victim of violence and a witness to the murder of his wife and child who experienced deep trauma for two years. The study aims to determine how PTSD is represented in this film. The approach used is John Fiske's semiotics, which includes levels of reality, representation, and ideology. The results of the study show that PTSD in the film is represented through 31 scenes that display symptoms such as re-experiencing symptoms, avoidance symptoms, arousal and reactivity symptoms, and cognition and mood symptoms. Cinematic elements such as dark lighting, silent space, and close-up camera composition strengthen the representation of psychological trauma. Ideologically, this film raises criticism of the system that passively handles victims as a whole, and shows a tendency towards vigilantism as a result of untreated trauma. This research is crucial for understanding how popular media, particularly films, can shape public perceptions of mental health and violence. The findings can also open up discussions about the importance of ethical and accurate representation of psychological conditions in audiovisual media.